Study of corrosion resistance of metal beryllium during thermocycling in vapour-argon conditions - Akhanov А.М.; Kulsartov Т.В.; Shakirov Б.Б.; Zaurbekova Ж.А. (Recent Contributions to Physics, 2024)
Experimental results are presented to study the corrosion resistance of metal beryllium (MB) during thermocycling in a steam-argon environment at temperatures from 600 to 900˚C. The aim of the study was to determine the kinetic parameters of corrosion processes and the rate of interaction of water vapour with the beryllium surface. The methodology involved cyclic heating and cooling of MB samples followed by mass loss measurements, visual inspection of the surface and estimation of kinetic parameters. As a result of experiments, the corrosion activation energy and pre-exponential factor were established. A significant increase in the corrosion rate with increasing temperature was demonstrated, which was attributed to the destruction of the oxide film and surface development of the samples. The obtained results have practical significance for ensuring the reliability and safety of beryllium use at high temperatures, especially in fusion and fission reactors. The study makes a significant contribution to the understanding of the corrosion behavior of MB during thermal cycling, providing valuable experimental data required for the design and operation of advanced high-temperature beryllium composites. The practical significance of the work is to increase the safety of installations and the durability of materials used in nuclear energy.